Perilaku Kesehatan Reproduksi Anak Perempuan Korban Trafficking di Manado - Sesca Diana Solang, Ira Paramastri, Budi Wahyuni (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: There were 23 girls who escaped from bar “F” in Timika Province of Papua. In 29 August 2002 during medical examination, it was found that one of the girls suffered from HIV/AIDS, others had sexual diseases, and there were some of them who were pregnant. The government paid attention to them and hence, they were invited to a skill course and will be given an asset; nevertheless, only five girls who attended.Objective: This research was aimed to find out knowledge of girls who were being prostitute regarding the threat of reproductive health disease, role of customer, procuress, health care provider, friend and family in giving support on the unwanted pregnancy, sexual transmitted disease (STD) and HIV/AIDS as well as how is the reproductive health behavior toward prevention of unwanted pregnancy, STD and HIV/AIDS during trafficking in Timika.Method: This research was an explorative qualitative one and it was conducted with focus group discussion toward research subject of girls who were being prostitute in Timika and in-depth interview toward research subject and program manager in the provincial level as informant key. The subjects were chosen with purposive sampling that used selected criteria. Qualitative data analysis was used from data collection until forming an explanation of data validity by using source and method triangulation.Result: In general, AYLA did not experience unwanted pregnancy because they used contraception. Condom can be obtained from health care provider or bought to be offered to their guest when having sexual relationship although most of the guests refused to use it. This condition showed the low bargaining position of girls who were being prostitute in the transaction process. People surrounding girls who were being prostitute has reminded each other to have self protection toward prevention of unwanted pregnancy, STD and HIV/AIDS with contraception. They know the risk if they did not use condom in having sexual relationship. The low bargaining position caused girls who were being prostitute had high risk toward reproductive health disease and could not have safe sex in order to be avoided from the transmission of STD even HIV/AIDS.Conclusion: Most girls who were being prostitute already know unwanted pregnancy, STD and HIV/AIDS, but they still have bad attitude and behavior on the risk of sexual disease when their guests were not using condom because of girls who were being prostitute low bargaining position and behavior on washing reproductive organ with toothpaste after having sexual relationship caused irritation and reproductive system disorder.Keywords: reproductive health behavior, girl, sacrifice trafficking